Simulação dos movimentos mandibulares baseado em colisões com e sem anteposição dos discos articulares - Cunha, Deivith Gonçalves da (Universidade do Vale do Rio dos Sinos, 2015)
The use of medical simulators is of great importance for the study, diagnosis and decision about how best to treat numerous diseases. A condition that affects many people is the displacement or dysplasia of temporomandibular joint discs bringing major disruptions in the process of opening and closing the mouth and severe pain when chewing. This study aims to model the mandibular displacements based on collisions between the condyles and temporal fossa, and the disc with pathology interference on jaw motion trajectory. Real data as three-dimensional models of bones reconstructed from CT images and articular disc reconstructed from RM images was used as model parameters. The Tempormandibular joint motion model is based on Posselt’s mandibular movement joined to the processing of collisions between anatomical parts in question using physics laws. As a result is presented comparisons of motion trajectories between a healthy joint and a joint with pathology related to articular disk. In the motion carried by an ATM with disk fronting , the jaw is prevented from moving correctly, making it impossible to fully open the mouth.
Keywords: Computação gráfica; Articulação temporomandibular; Colisões; Computer graphics; Temporomandibular joints; Collisions; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação